(untitled) (Revista Argentina de Cirugía, 2021)
ABSTRACT Background: Background: gallstone ileus is a rare complication of cholelithiasis, more commonly seen in the elderly. It is the cause of 1 to 4% of all mechanical intestinal obstruction and it has a high rate of morbidity and mortality. Objective: to describe our experience and results in the management of gallstone ileus. Materials and methods: We included all patients with diagnosis of gallstone ileus treated between January 2000 and December 2009. Demographic characteristics, personal and biliary history, clinical presentation and diagnostic methods, preoperative stay and type of surgery, perioperative complications and hospital stay, were analyzed. Results: 20 patients were enrolled, 65% were women. Average age was 82.9 years (median, 83 years). 80% of patients had comorbidities. Bowel obstruction was the most frequent clinical presentation. The preoperative diagnosis of gallstone ileus was made in 80% of cases. In 18 patients a video-assisted enterolithotomy was done. A 10% morbidity and 5% mortality was observed. Conclusion: the video-assisted approach of gallstone ileus is a safe and efficient procedure.